Seasonal variations in distribution, heavy metal uptake and proline production of native plants growing on Pb-contaminated site in Ibadan, South-Western, (2015)
Effects of seasonal variations on metal (Lead, Chromium and Cadmium) uptake, proline concentration, density and distribution of metallophytes inhabiting heavy metal polluted site in Ibadan, South-Western Nigeria were investigated. Vegetation surveys and Relative Importance Values (RIV) of different plant species were carried out both at the rainy and dry seasons. The metal uptake and partitioning in plants at different seasons as well as proline content were also determined. The results showed that the Relative Importance Value (RIV), metal uptake and proline production by plants varied depending on the prevailing environmental conditions. During both sampling seasons, same plant species were enumerated on the contaminated site. However, their RIV varied in the two seasons. Sporobolus. pyramidalis was prevalent in the rainy season while Imperata cylindrica had the highest RIV during the dry season. Heavy metal accumulation in different plant species also differed depending on the sampling period and higher concentrations of metals were accumulated during the rainy season compared to the dry season except in Gomphrena celosioides with Pb being the highest at both seasons. The proline concentrations were also species and season dependent. The concentrations varied in different plant species and G. celosioides accumulated more during both seasons while Eleucine indica and Rhyncospora corymbosa had higher concentrations during the dry season compared to rainy season. Plant species abundance, metal uptake and osmolyte production by metallophytes are therefore dependent on the prevailing environmental conditions.